2021
DOI: 10.1093/trstmh/trab135
|View full text |Cite
|
Sign up to set email alerts
|

The immature platelet fraction, a predictive tool for early recovery from dengue-related thrombocytopenia: a prospective study

Abstract: Background There is a paucity of predictive factors for early recovery from thrombocytopenia related to dengue. The immature platelet fraction (IPF%) is reflective of megakaryopoiesis and may correlate with recovery from dengue-related thrombocytopenia. Our objective was to assess the predictive value of IPF% on days 2 and 3 of illness for recovery from dengue-related thrombocytopenia. Methods A prospective study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…As the whole blood counts were dynamic throughout the pathogenic process, a subgroup analysis of sampling time was conducted, but the pooled effect showed no significant difference. Additionally, some studies revealed that atypical lymphocyte count, immature platelet fraction and triple positivity for NS1, Ig M and Ig G would be predictive for SD [56][57][58], although them couldn't be included in this meta-analysis. Further studies should be performed to identify in the future.…”
Section: Plasma Biomarkersmentioning
confidence: 99%
“…As the whole blood counts were dynamic throughout the pathogenic process, a subgroup analysis of sampling time was conducted, but the pooled effect showed no significant difference. Additionally, some studies revealed that atypical lymphocyte count, immature platelet fraction and triple positivity for NS1, Ig M and Ig G would be predictive for SD [56][57][58], although them couldn't be included in this meta-analysis. Further studies should be performed to identify in the future.…”
Section: Plasma Biomarkersmentioning
confidence: 99%
“…The fact that the immature platelet fraction (a surrogate for thrombopoiesis) in the peripheral blood is significantly lower in patients with severe dengue supports this hypothesis. [38] This is however difficult to study definitively, as bone marrow aspiration/biopsy is rarely performed in patients with Dengue infection. A variety of clinical parameters have been proposed which may enable early identification of patients who are likely to develop severe thrombocytopaenia.…”
Section: Thrombocytopaeniamentioning
confidence: 99%
“…Within 48hours after the peak IPF % was reached, platelet recovery was observed regardless of severity. [100] The increased risk of adverse outcomes with secondary dengue infection is well documented. Indeed , there is a correlation between the serologic subtype of dengue and various haematologic parameters.…”
Section: Implications For Prognosis and Risk Stratificationmentioning
confidence: 99%
“…Previous research has highlighted the utility of various cell population data (CPD) in measuring immune response, particularly in cases with viral origins [21,22]. This has led to the development of an intensive care infection score (ICIS), mirroring the functionality of procalcitonin (PCT) in identifying bacterial infections in hospitalized patients [23,24].…”
Section: Introductionmentioning
confidence: 99%